Editorial 17.5: Strengthening our focus for a post-COVID-19 environment: Learnings from a pandemic in higher education - Crawford, Joseph; Percy, Alisa; Kelder, Jo-Anne; Butler-Henderson, Kerryn (Journal of University Teaching and Learning Practice, 2020)
The year 2020 will unlikely be one that any member of the higher education community will forget. It has posed challenges and opportunities to rethink aspects of tertiary learning and teaching, and also confirmation of some of the better practices we have engaged in. For some, the novel coronavirus pandemic has forced bad practice – such as simple and rapid digitalisation of existing curriculum – often bundled into the pedagogically-ambiguous ‘emergency remote teaching’ or ERT (Toquero, 2020). The intense pressure for academics to deliver curriculum online, typically to the exception of time for comprehensive academic development and upskilling.The practice for an overnight transition to online learning, while deemed by many to have been essential at the time, has created a myriad of future decisions to be actioned across the sector. These range from deploying future academic development workshops to transform the workforce for continued online learning to employment of educational technologists, learning designers, or similar to enable purposeful decisions of pedagogy within online learning environments. Financial constraints have tempered the deployment of additional resources, with institutions suffering from financial modelling unexpected in late-2019 budget forecasting meetings. A reduction in student enrolments from international markets offers complexity for higher education exporter nations like Australia (Marshman & Larkins, 2020). Nonetheless, there has been a resilience from the sector to ensure continuity of education under all circumstances.The role of journals like the Journal of University Teaching and Learning Practice during the pandemic has been to support timely publication of evidence-based practices for responses to COVID-19. This has included a need to balance the acceptance of manuscripts with pre-COVID-19 data and implications, and those authors contributing to the exponentially expanding knowledge base for teaching and learning during COVID-19. For the former, we have encouraged authors during final acceptance to reflect on their work’s role in enabling a positive response to the pandemic. For those in the latter, we have ensured that writers have considered the broader implications of their work beyond the pandemic. These decisions support manuscripts publishing in JUTLP to contribute to the contemporary landscape, and also beyond the pandemic.